1980
DOI: 10.1159/000232617
|View full text |Cite
|
Sign up to set email alerts
|

Cytofluorometric Analysis of Anaphylactic Secretion of 5-Hydroxytryptamine and Heparin from Rat Mast Cells

Abstract: Actively sensitized rat mast cells were stimulated to secretion in vitro by means of an anaphylactic IgE antigen reaction or with polymyxin B. Release of 5-hydroxytryptamine (5-HT) and heparin from the cells and from individual granules, extruded or displaced from stimulated cells with micromanipulation, was quantitated cytofluorometrically. Several similarities in action between the two secretagogues were found. All extruded and some intracellular granules from stimulated cells lacked 5-HT, and no heparin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Intradermal injection of other agents that induce itch in humans, such as histamine, compound 48/80, substance P, and proteases, elicited little or no scratching in Sprague-Dawley rats (Thomsen et al, 2001;Jinks and Carstens, 2002). Rodent mast cells contain relatively high concentrations of 5-HT (Gustafsson, 1980;Graziano, 1988;Purcell et al, 1989), consistent with a role for 5-HT as an itch mediator in rodents.…”
Section: -Ht 2 Receptor Involvement In Acute Scratchingsupporting
confidence: 57%
“…Intradermal injection of other agents that induce itch in humans, such as histamine, compound 48/80, substance P, and proteases, elicited little or no scratching in Sprague-Dawley rats (Thomsen et al, 2001;Jinks and Carstens, 2002). Rodent mast cells contain relatively high concentrations of 5-HT (Gustafsson, 1980;Graziano, 1988;Purcell et al, 1989), consistent with a role for 5-HT as an itch mediator in rodents.…”
Section: -Ht 2 Receptor Involvement In Acute Scratchingsupporting
confidence: 57%
“…Previous reports that opiates can exacerbate itch sensation in humans (Lanz et al, 1982;Stenseth et al, 1985;Ballantyne et al, 1988) would predict an increase in 5-HT-evoked scratching, which was not observed presently. 5-HT is an inflammatory mediator associated with pain and hyperalgesia (Jensen et al, 1991;Taiwo and Levine, 1992;Abbott et al, 1996) and is liberated from rodent mast cells and platelets in many inflammatory responses (Gustafsson, 1980;Purcell et al, 1989). In humans, intradermal injection (up to 20 g/20 l) (Keele and Armstrong, 1964;Fjellner and Hägermark, 1979;Hägermark, 1995) or iontophoresis of 5-HT (1%) (Weisshaar et al, 1997) is weakly pruritic.…”
Section: Discussionmentioning
confidence: 99%
“…We have used a cy tofluorometric method to measure heparin release [Gimimsori and Enerback. 1980;Gustavsson, 1980] utilizing the weakly fluorescent dye, berberine, which strongly increases its quantum yield of fluorescence upon binding to heparin. This method can be used to measure the heparin content of individual mast cells by microscopic fluorometry [Enerback.…”
Section: Introductionmentioning
confidence: 99%